GASKAP-HI pilot survey science I: ASKAP zoom observations of Hi emission in the Small Magellanic Cloud. (7th February 2022) - Pingel, N. M.; Dempsey, J.; McClure-Griffiths, N. M.; Dickey, J. M.; Jameson, K. E.; Arce, H.; Anglada, G.; Bland-Hawthorn, J.; Breen, S. L.; Buckland-Willis, F.; Clark, S. E.; Dawson, J. R.; et al.
Abstract: We present the most sensitive and detailed view of the neutral hydrogen ( HI ) emission associated with the Small Magellanic Cloud (SMC), through the combination of data from the Australian Square Kilometre Array Pathfinder (ASKAP) and Parkes (Murriyang), as part of the Galactic Australian Square Kilometre Array Pathfinder (GASKAP) pilot survey. These GASKAP-HI pilot observations, for the first time, reveal HI in the SMC on similar physical scales as other important tracers of the interstellar medium, such as molecular gas and dust. The resultant image cube possesses an rms noise level of 1.1 K ( 1.6 mJy beam^-1 ) per 0.98 km s^-1 spectral channel with an angular resolution of 30^′′ ( 10 pc ). We discuss the calibration scheme and the custom imaging pipeline that utilises a joint deconvolution approach, efficiently distributed across a computing cluster, to accurately recover the emission extending across the entire 25 deg^2 field-of-view. We provide an overview of the data products and characterise several aspects including the noise properties as a function of angular resolution and the represented spatial scales by deriving the global transfer function over the full spectral range. A preliminary spatial power spectrum analysis on individual spectral channels reveals that the power law nature of the density distribution extends down to scales of 10 pc. We highlight the scientific potential of these data by comparing the properties of an outflowing high-velocity cloud with previous ASKAP+Parkes HI test observations.